Rationale and Design of the Pediatric Critical Illness Stress-Induced Immune Suppression (CRISIS) Prevention Trial - Carcillo, Joseph (2009)
Despite implementation of CDC recommendations and bundled interventions for preventing catheter-associated blood stream infection, ventilator-associated pneumonia, or urinary catheter–associated infections, nosocomial infections and sepsis remain a significant cause of morbidity and mortality in critically ill children. Recent studies suggest that acquired critical illness stress-induced immune suppression (CRISIS) plays a role in the development of nosocomial infection and sepsis. This condition can be related to inadequate zinc, selenium, and glutamine levels, as well as hypoprolactinemia, leading to stress-induced lymphopenia, a predominant T(H)2 monocyte/macrophage state, and subsequent immune suppression. Prolonged immune dysfunction increases the likelihood of nosocomial infections associated with invasive devices. Although strategies to prevent common complications of critical illness are routinely employed (eg, prophylaxis for gastrointestinal bleeding, thrombophlebitis), no prophylactic strategy is used to prevent stress-induced immune suppression. This is the authors’ rationale for the pediatric CRISIS prevention trial (NCT00395161), designed as a randomized, double-blind, controlled clinical investigation to determine if daily enteral supplementation with zinc, selenium, and glutamine as well as parenteral metoclopramide (a dopamine 2 receptor antagonist that reverses hypoprolactinemia) prolongs the time until onset of nosocomial infection or sepsis in critically ill children compared to enteral supplementation with whey protein. If effective, this combined nutritional and pharmacologic approach may lessen the excess morbidity and mortality as well as resource utilization associated with nosocomial infections and sepsis in this population. The authors present the design and analytic plan for the CRISIS prevention trial.